Structure of partly quenched molten copper chloride - Pastore, G; Tatlipinar, H; Tosi, MP (GORDON BREACH SCI PUBL LTD, 1996)
The structural modifications induced in a model of molten CuCl by quenching the chlorine component into a microporous disordered matrix are evaluated using the hypernetted-chain closure in Ornstein-Zernike relations for the pair distribution functions in random systems. Aside From obvious changes in the behaviour of long-wavelength density fluctuations, the main effect of partial quenching is an enhanced delocalization of the Cu+ ions. The model suggests that the ionic mobility in a superionic glass is enhanced relative to the melt at the same temperature and density. Only very minor quantitative differences are found in the structural functions when the replica Ornstein-Zernike relations derived by Given and Stell for a partly quenched system are simplified to those given earlier by Madden and Glandt.
Keywords: ionic mobility; superionic glass; SILVER-IODIDE MELTS; RANDOM-MEDIA; FLUID DISTRIBUTIONS; ARBITRARY MATRICES; EQUATIONS; EQUILIBRIUM; POTENTIALS; HALIDE; Chemistry; Physics